Rethinking the Economic Implications of Leadership Deficit in Nigeria - Bamikole Adeyanju, Joseph; Omolola Adeyanju, Faith (Kashere Journal of Politics and International Relations, 2023)
This study interrogates the economic implications of leadership deficit in Nigeria. From time immemorial, national development which is largely hinged on economic development has been a major discourse among scholars, while economic development has been one of the relevant goals of the less developed countries. One of the major reasons adduced for a truncated national development in Nigeria is leadership deficit. Political leaders who are at the center of determining strong economy have failed repeatedly in their policies, they amass wealth for themselves to the detriment of the people, therefore painting themselves as national capitalists. Given that leadership in Nigeria is deficient, it in turn reverberates inimically on her national development. In this vein, this paper historically examined how herculean is the effect of leadership deficit on Nigerian economy and the extent to which it could be remedied. Through the use of textual data and thematic analysis, this paper draws the nexus between leadership and development and also deduces pathways for a vibrant Nigerian economy.